Improved multiparametric scrape loading-dye transfer assay for a simultaneous high-throughput analysis of gap junctional intercellular communication, cell density and viability - Dydowiczová, Aneta; Brózman, Ondřej; Babica, Pavel; Sovadinová, Iva (Scientific reports, 2020)
Gap junctional intercellular communication (GJIC) is a vital cellular process required for maintenance of tissue homeostasis. In vitro assessment of GJIC represents valuable phenotypic endpoint that could be effectively utilized as an integral component in modern toxicity testing, drug screening or biomedical in vitro research. However, currently available methods for quantifying GJIC with higher-throughputs typically require specialized equipment, proprietary software and/or genetically engineered cell models. To overcome these limitations, we present here an innovative adaptation of traditional, fluorescence microscopy-based scrape loading-dye transfer (SL-DT) assay, which has been optimized to simultaneously evaluate GJIC, cell density and viability. This multiparametric method was demonstrated to be suitable for various multiwell microplate formats, which facilitates an automatized image acquisition. The assay workflow is further assisted by an open source-based software tools for batch image processing, analysis and evaluation of GJIC, cell density and viability. Our results suggest that this approach provides a simple, fast, versatile and cost effective way for in vitro high-throughput assessment of GJIC and other related phenotypic cellular events, which could be included into in vitro screening and assessment of pharmacologically and toxicologically relevant compounds.
Keywords: kultivované buňky; Cells, Cultured; Gap Junctions; Microscopy, Fluorescence; Rats; Image Processing, Computer-Assisted; mezibuněčná komunikace; Molecular Imaging; Cell Communication; Animals; mezerový spoj; viabilita buněk; molekulární zobrazování; Cell Count; zvířata; krysa rodu Rattus; počítačové zpracování obrazu; počet buněk; Cell Survival; fluorescenční mikroskopie